Coraline eaudiobook - Gaiman, Neil (2003)
New York Times bestselling and Newbery Medal-winning author Neil Gaiman's modern classic, Coraline —also an Academy Award-nominated film ""Coraline discovered the door a little while after they moved into the house...."" When Coraline steps through a door to find another house strangely similar to her own (only better), things seem marvelous. But there's another mother there, and another father, and they want her to stay and be their little girl. They want to change her and never let her go. Coraline will have to fight with all her wit and courage if she is to save herself and return to her ordinary life. Neil Gaiman's Coraline is a can't-miss classic that enthralls readers age 8 to 12 but also adults who enjoy a perfect smart spooky read.